Efektivitas Penyiram Tanaman Bawang Merah Otomatis Menggunakan Sensor Moisture Soil dan Modul GSM - Irfianto, Aliffian; Puspitasari, M. Dewi Manikta; Indrawati, Elsanda Merita; Mahdiyah, Agus; Suwardono, Agus (Nusantara of Engineering (NOE), 2025)
The product supporting the performance of shallot farmers is an automatic shallot plant watering tool used to make the watering process on shallots more effective. The tool automatically waters shallot plants based on the soil moisture level detected by the soil moisture sensor so that the watering process becomes more efficient in watering time and the work saves more human energy and water. The purpose of this study is (1) to determine the effectiveness of the automatic watering tool on shallot plants, and (2) to determine the soil moisture level needed by shallot plants. The method used is a quantitative research method with t-test analysis. The results of the test based on the duration of watering and water usage obtained an automatic watering tool 3.74 s faster than manual watering and an automatic watering tool 5.67 l more efficient than manual watering. This shows that the automatic watering tool for shallot plants using a soil moisture sensor and gsm module is more effective and makes it easier for shallot farmers compared to manual watering for farmers.